The New Facilitators’ Strategies in Managing Online Discussion of the Second IMOOC - hidayah nor (ELT Echo : The Journal of English Language Teaching in Foreign Language Context, 2019)
The second Indonesian Massive Open Online Course are the collaboration between Regional English Language Office (RELO) and the Embassy of United States of America in Jakarta introducing the use of technology for autonomous learning as the new insight for the participants that focuses on recruiting pre-service English teachers, English Teachers (Elementary school, junior high school, or senior high school teachers), English lecturers in the university around Indonesia. The purpose of this research was to describe qualitatively the second MOOC new facilitators’ strategies in managing online discussion and whether they were affected by their own facilitators’ strategies when they joined as the participants of the first Indonesian MOOC. There were eight new facilitators who came from different regions in Indonesia such as Rembang, Salatiga, Surabaya, Solo, Semarang, Malang, and Banjarmasin. The data were collected through a Questionnaire. The results of this research shown that there are various strategies that have been applied by the new facilitators including design questions that particularly get on-topic discussion carefully, help online learners in providing a guideline for the preparation on-topic responses, present rules for those who choose off-topic comments explicitly, state the expectation for online discussions participants to stay on a topic, set alternative locations for off-topic discussions, screen all postings and put off-topic posts to alternative locations with an explanation to participants, incorporate a reminder that responses stay on a topic with all posted questions, reword the original question when responses are going in the wrong direction, provide discussion summary regularly, give warning privately and corrective suggestions to learners who submit off-topic comments, give a reward for those who keep on a topic, and offer a grade for those who keep on a topic. This is really helped the second Indonesian MOOC participants to make the discussions contains more cognitive presences and they can accomplish the course and gain a new knowledge from this online course. Keywords: IMOOC, Facilitators’ strategies, Indonesian Massive Open Online Course, Online discussion